(untitled) (ETNOSIA : Jurnal Etnografi Indonesia, 2024)
Currently, climate change poses a threat to agriculture, including in the Bengawan Solo watershed. This study aims to explore farmers’ perceptions of climate change and understand the adaptations they undertake. The study was conducted in Mejuwet Village, Sumberrejo Subdistrict, Bojonegoro Regency, using qualitative. This study involved six informants, consisting of three farmers and three farm laborers. The selection of informants was based on the criterion of having more than ten years of experience in farming. Data was collected using in-depth interview and observation. Subsequently, the data were analyzed using an interactive model. The study indicates that farmers have knowledge of and can articulate the climate changes they have encountered, albeit with some limitations in understanding, and they actively participate in adaptation efforts. Farmer adaptation encompasses technical modifications like establishing planting schedules and methods, and choosing high-quality varieties. Cultural adaptation encompasses traditions like the wiwitan ceremony. Social adaptation involves using social connections and prioritizing investments in children’s schooling. Lastly, economic adaptation involves broadening job opportunities and liquidating assets.